Long‐term effects of repetitive head impacts on gray matter cortical thickness. (31st December 2021) - Brekke, Bailee; DeVivo, Renee; McKee, Ann C.; Stein, Thor D.; Tripodis, Yorghos; Phelps, Alyssa; Weller, Jason; Martin, Brett M; Palmisano, Joseph; Steinberg, Eric; Turk, Katherine W; Budson, Andrew; et al.
Abstract: Background: Repetitive head impact (RHI) exposure has been associated with the neurodegenerative disease chronic traumatic encephalopathy (CTE). Magnetic resonance imaging (MRI) and postmortem research suggest frontotemporal atrophy may be characteristic of CTE. The late effects of RHI on cortical volume remain poorly understood due to focus on male former professional American football players and lack of examination of specific lobar gyri. We leveraged the Boston University Alzheimer's Disease Research Center (BU ADRC) to compare frontal, temporal, and parietal gyri gray matter thickness between participants with and without RHI exposure. Method: 39 participants exposed to RHI and 33 similar‐aged (+/‐ 5 years) participants without RHI from the BU ADRC, all spanning the cognitive continuum, underwent MRI on a 3T Philips. Freesurfer was used to derive regional gray matter cortical thickness values. For the frontal, temporal, and parietal lobes, we computed mean composites of superior, middle, and inferior gyri gray matter measures. Analysis of covariance compared participants with and without RHI, controlling for age, sex, race, education and hippocampal volume. Result: Mean age was 62.31 (SD=8.87), 34 (47.2%) were female, and 65 (90.3%) were White. Of the RHI group, 23 (59.0%) played American football, 9 (23.1%) ice hockey, 5 (12.8%) were boxers, and 3 (7.7%) were amateur wrestlers. Compared to non‐RHI, RHI‐exposed participants had decreased gray matter thickness of superior (marginal mean diff [MD]=0.10, p<0.01) and middle frontal gyri (MD=0.06, p=0.03), and the middle temporal gyrus (MD=0.07, p=0.03). There were no differences in gray matter thickness for inferior frontal, superior or inferior temporal, or parietal gyri. Because the CTE tau lesion is uniquely at the sulcal depths, we examined the gray matter thickness of the banks of superior temporal sulcus and RHI participants had reduced thickness (MD=0.09, p=0.02). Conclusion: Frontotemporal atrophy may be a characteristic late effect of RHI exposure. Further examination of thickness of different lobar gyri in the setting of RHI may facilitate disease differentiation. Larger samples will be important to examine how the effects of RHI on gray matter cortical thickness differ by sex, sport played, etc.